Taking Flight with Copilot. - BIRD, CHRISTIAN; FORD, DENAE; ZIMMERMANN, THOMAS; FORSGREN, NICOLE; KALLIAMVAKOU, EIRINI; LOWDERMILK, TRAVIS; GAZIT, IDAN (Communications of the ACM, 2023)
The article evaluates GitHub's Copilot, an AI (Artificial Intelligence) pair programmer that simulates two programmers working together synchronously.